Women's Leadership in the Party (Case Study: Grace Natalie's Leadership as Chair of PSI for the 2014-2021 period) - Sitompul, Gita Tiurma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Women's representation in politics is a form of women's participation in supervising every policy process so that the impact of the policy will be in accordance with gender-based interests. Women's representation in the process of formulating and determining policies is a concrete step to support the realization of justice and equality for women (Firman, 2018). In this context, women have a broad role in joining women's organizations and political parties to provide adequate space in channeling their aspirations. The lack of responsive gender policies makes the role of women in political contestation not yet encourage the level of representation in politics (Priandi & Roisah, 2019). The active role of women can be realized through participation by carrying out women's obligations as citizens, namely influencing the process of determining public policies through a representative mechanism that can accommodate women's interests (Rodiyah, 2016). This study seeks to find out whether there is an influence between female leaders in political parties (this paper focuses on PSI Indonesia) and the political participation of other female political party members.